Challenges facing adult learners: a case study of postgraduate students / Azelin Mohamed Noor - Mohamed Noor, Azelin (2007)
This case study investigates the challenges of adult learners as they seek a master’s degree course. Adapting the conceptual framework of Cross (1981), Hillage & Aston, (2001) and Mackeracher, Suart & Potter (2006), three main challenges were discussed; physical and material / situational, structural and attitudinal. Two instruments; diaries and interviews were utilized to uncover the challenges of three adult learners. Twenty varieties of challenges emerged from the data collected. All three categories of challenges were found as well as academic challenges. Although not fully generalizable, this study presents some interesting and constructive information. The challenges are the lack of support, health, multiple-conflicting responsibilities, job commitments, the lack of time, financial constraint, guilt, distance to be travelled, being unmarried, the lack of concentration, the lack of confidence, the lack of motivation, the lack of appropriate provisions, inappropriate schedules, writing academic texts, understanding academic texts, assignment workload, problems with vocabulary and grammar, and unclear and unacceptable methods of evaluation. Coping strategies towards some of the physical and material / situational challenges were recommended. To overcome the challenges from the lack of time, bringing reading materials to read while out with loved ones and to double the use of activities at work for the use of the master’s assignments were suggested. To overcome stress, taking unpaid leave was advised. To overcome financial constraint, delaying the purchase of expensive books and reducing entertainment allocation were offered. To overcome multiple-conflicting responsibilities, acknowledging the importance of the various responsibilities and accepting one’s limitations were proposed. The implications of the study include the value of support and encouragement from those near at heart, the importance of time management, the need for endurance, the requirement for continued focus, the importance of obtaining consensus on class schedules and postgraduate adult learners do not necessarily possess essential academic skills. Suggestions for further research include a similar research which is conducted over a longer period of time, a study on the interactions between the different varieties of challenges and a comparative study to examine the differences between the challenges of local adult learners and those from foreign universities.